1991
DOI: 10.1128/iai.59.3.913-924.1991
|View full text |Cite
|
Sign up to set email alerts
|

Antigens of Actinobacillus actinomycetemcomitans recognized by patients with juvenile periodontitis and periodontally normal subjects

Abstract: Most juvenile periodontitis patients respond to infection by Actinobacillus actinomycetemcomitans by producing serum antibodies. Specific antigens inducing the humoral immune response have not been identified, nor has the role of the resulting antibodies in disease progression been determined. Adsorbed and unadsorbed sera from juvenile periodontitis patients and normal subjects were analyzed by enzyme-linked immunosorbent assay and Western blots (immunoblots), using digested and undigested bacterial sonicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 42 publications
6
71
0
Order By: Relevance
“…Various investigators have demonstrated that patients with localized juvenile periodontitis exhibit elevated serum IgG antibody to A. actinomycetemcomitans and that the immunodominant antigen of the organism is a capsular-like polysaccharide or the polysaccharide portion of lipopolysaccharide (6,10,23,26,36). In addition, serum IgG antibody to A. actinomycetemcomitans elevated in periodontitis patients has been reported to enhance in vitro phagocytosis of the organism by human neutrophils (3,27,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various investigators have demonstrated that patients with localized juvenile periodontitis exhibit elevated serum IgG antibody to A. actinomycetemcomitans and that the immunodominant antigen of the organism is a capsular-like polysaccharide or the polysaccharide portion of lipopolysaccharide (6,10,23,26,36). In addition, serum IgG antibody to A. actinomycetemcomitans elevated in periodontitis patients has been reported to enhance in vitro phagocytosis of the organism by human neutrophils (3,27,34).…”
Section: Discussionmentioning
confidence: 99%
“…The serotype-specific antigens of serotypes d and e have not yet characterized. Patients with localized juvenile periodontitis exhibit elevated serum antibody levels to SPA of A. actinomycetemcomitans serotype b (6,23,26,36). However, the role of serum SPA-specific antibodies in host responses to A. actinomycetemcomitans is poorly understood.…”
Section: Actinobacillusmentioning
confidence: 99%
“…ELISA Specific IgG antibody titers were determined by ELISA as previously described (49). Ultrasonically disrupted cells (10 [xg protein per ml) and purified antigen preparations (5 jig dry weight per ml) in 100 mM carbonate buffer (pH 9.6) were coated onto the surface of polystyrene microtest plate wells (Flow Laboratories) for 2 h at room temperature and overnight at 4°C respectively.…”
Section: Antigen Preparationsmentioning
confidence: 99%
“…Western immunoblots of the whole-cell sonic extract and purified antigens were prepared by the method of Towbin et al (55) as described by Sims et al (49). Samples were suspended in sample buffer (100 mM Tris, 10% sucrose, 1% SDS, 1% 2-mercaptoethanol [pH 6.8]) at a dry weight concentration of 0.5 mg/ ml and heated in a boiling water bath for 4 min.…”
Section: Immunobtotsmentioning
confidence: 99%
See 1 more Smart Citation